2020
DOI: 10.1111/all.14526
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL‐25, IL‐33, and TSLP in triggering united airway diseases toward type 2 inflammation

Abstract: Under the concept of "united airway diseases," the airway is a single organ wherein upper and lower airway diseases are commonly comorbid. The upper and lower airways are lined with respiratory epithelium that plays a vital role in immune surveillance and modulation as the first line of defense to various infective pathogens, allergens, and physical insults. Recently, there is a common hypothesis emphasizing epithelium‐derived cytokines, namely IL‐25, IL‐33, and TSLP, as key regulatory factors that link in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 105 publications
5
120
0
1
Order By: Relevance
“…We propose a concept of “adult‐onset eosinophilic airway diseases” including asthma, N‐ERD, ABPA/ABPM, CRSwNP/eosinophilic CRS, and EGPA. Common pathophysiology such as EETosis/mucus plug formation and common genetic backgrounds including TSLP/IL‐33 pathway genes seem to underlie these diseases 153,154 . In addition, each disease exhibits a specific pathophysiology such as mast cell and platelet activation in N‐ERD, fungal sensitization in ABPA/ABPM, abnormality in coagulation/fibrinolysis pathway in CRSwNP/eosinophilic CRS and autoimmunity in EGPA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose a concept of “adult‐onset eosinophilic airway diseases” including asthma, N‐ERD, ABPA/ABPM, CRSwNP/eosinophilic CRS, and EGPA. Common pathophysiology such as EETosis/mucus plug formation and common genetic backgrounds including TSLP/IL‐33 pathway genes seem to underlie these diseases 153,154 . In addition, each disease exhibits a specific pathophysiology such as mast cell and platelet activation in N‐ERD, fungal sensitization in ABPA/ABPM, abnormality in coagulation/fibrinolysis pathway in CRSwNP/eosinophilic CRS and autoimmunity in EGPA.…”
Section: Resultsmentioning
confidence: 99%
“…Common pathophysiology such as EETosis/ mucus plug formation and common genetic backgrounds including TSLP/IL-33 pathway genes seem to underlie these diseases. 153,154 In addition, each disease exhibits a specific pathophysiology such as mast cell and platelet activation in N-ERD, fungal sensitization in ABPA/ABPM, abnormality in coagulation/fibrinolysis pathway in CRSwNP/eosinophilic CRS and autoimmunity in EGPA. The clinical efficacy of anti-IL-5 treatments was also variable among the diseases, high for eosinophilic asthma, ABPA/ABPM and EGPA, whereas low for N-ERD and CRSwNP/eosinophilic CRS (Table 1).…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Because of the difference in smooth muscle and blood sinus between the lower and upper airways, whether remodelling involves in AR is still controversial. Some researches have implied the existence of remodelling in AR [10,11]. Hence, we speculated that refractory AR might be linked to remodelling of the nasal mucosa.…”
Section: Introductionmentioning
confidence: 90%
“…However, whether tissue remodelling of the nasal cavity occurs in AR is uncertain. Nasal remodelling, including goblet cell hyperplasia and collagen deposition, has been reported to occur in AR mice [10,11], whereas other studies have suggested that ani-mal models of AR involve microvascular remodelling of the nasal mucosa [42] and lung remodelling [43]. Additionally, remodelling of the nasal mucosa is reportedly more evident in AR patients with irreversible nasal obstruction [44].…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Furthermore, the level of TSLP expression in patients with asthma is correlated with airway obstruction and disease severity [12] . Moreover, some recent clinical studies using anti-TSLP mAb have yielded promising results [13] . However, these studies mainly employ intraperitoneal or subcutaneous injections, at present, while inhaled medications remain the mainstream approach for clinical asthma treatment, since they are less invasive than injections.…”
Section: Introductionmentioning
confidence: 99%